2008
DOI: 10.1002/bip.20925
|View full text |Cite
|
Sign up to set email alerts
|

Bruce Merrifield and solid‐phase peptide synthesis: A historical assessment

Abstract: Bruce Merrifield, trained as a biochemist, had to address three major challenges related to the development and acceptance of solid‐phase peptide synthesis (SPPS). The challenges were (1) to reduce the concept of peptide synthesis on a insoluble support to practice, (2) overcome the resistance of synthetic chemists to this novel approach, and (3) establish that a biochemist had the scientific credentials to effect the proposed revolutionary change in chemical synthesis. How these challenges were met is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 48 publications
2
38
0
4
Order By: Relevance
“…[3] Furthermore, the catalytic formation of long polypeptides from unactivated amino acids could be of interest for new synthetic strategies aimed at avoiding poor atom economy reagents, in addition to well-established solid-phase peptide synthesis methods. [6] In a previous study, we revealed the role of the (101) and (001) facets of anatase TiO 2 nanoparticles in activating adsorbed carboxylate moieties toward a nucleophilic attack of amines to form amides. [7] In the present study, we extend the investigation to the adsorption of glycine (Gly) vapors (with molecules in the nonionic HOOC-CH 2 -NH 2 form) by adopting the experimental procedure established for adsorbing Gly onto hydroxyapatite (HA) nanoparticles.…”
mentioning
confidence: 95%
“…[3] Furthermore, the catalytic formation of long polypeptides from unactivated amino acids could be of interest for new synthetic strategies aimed at avoiding poor atom economy reagents, in addition to well-established solid-phase peptide synthesis methods. [6] In a previous study, we revealed the role of the (101) and (001) facets of anatase TiO 2 nanoparticles in activating adsorbed carboxylate moieties toward a nucleophilic attack of amines to form amides. [7] In the present study, we extend the investigation to the adsorption of glycine (Gly) vapors (with molecules in the nonionic HOOC-CH 2 -NH 2 form) by adopting the experimental procedure established for adsorbing Gly onto hydroxyapatite (HA) nanoparticles.…”
mentioning
confidence: 95%
“…A terceira abordagem envolve o uso de enzimas que não sejam esterases ou proteases, e será exemplificada mais a seguir nesta seção. 66 As proteases são classificadas em 6 grupos, com base em seus sítios ativos (note-se que existem outras formas de classificação de proteases, como a que se baseia em sua forma de atuação sobre o substrato -endopeptidases, exopeptidases, etc): serina proteases (como a tripsina, quimiotripsina e subtilisina), 67 treonina proteases, 68 cisteína proteases (como a papaina e a bromelina), 69 aspartato protease (como a pepsina), 70 glutamato protease 71 e metaloprotease (como a termolisina). 72 A síntese de polipeptídeos catalisada por proteases pode ocorrer regida por um controle termodinâmico ou cinético.…”
Section: Poliamidas E Polipeptídeosunclassified
“…Bruce Merrifield was the first to recognize the usefulness of polymer-supported organic synthesis, and is best known for the invention and development of solid-phase peptide synthesis (SPPS), which revolutionized synthetic organic chemistry. [29] Merrifield planned to attach the C-terminal amino acid to an insoluble particle throughout the synthesis and to grow the peptide chain on that residue. [30] His first successful synthesis by SPPS was of the tetrapeptide, L-Leu-L-Ala-L-Gly-L-Val on nitrochloromethylphenyl polymer resin using benzyloxycarbonyl (Cbz)-protected amino acids (30% hydrogen bromide in acetic acid for the deprotection, N ,N -Dicyclohexylcarbodiimide (DCC) in DMF for the peptide-forming step, 2 N sodium hydroxide in ethanol for the peptide liberation step).…”
Section: Carboxylic Acid Linkersmentioning
confidence: 99%